2017
DOI: 10.7567/jjap.56.05ea03
|View full text |Cite
|
Sign up to set email alerts
|

Soft blanket gravure printing technology for finely patterned conductive layers on three-dimensional or curved surfaces

Abstract: In this paper, we report on a newly developed printing method called the “soft blanket gravure” (SBG) printing method, which is based on a conventional gravure offset printing method but unlike it, SBG printing uses a very soft and thick offset blanket. SBG printing onto various curved, nonplanar surfaces as well as on planar surfaces using silver ink was successfully demonstrated by optimizing printing conditions such as printing pressure and printing speed. Finely printed conductive silver lines with a 30 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Printing is very useful technique, since it enables rapid pattern formation at low cost. Flexographic printing [ 12 , 13 , 14 ], microcontact printing [ 15 ], gravure printing [ 16 ], gravure-offset printing [ 17 , 18 ], soft blanket gravure printing [ 19 ], reverse-offset printing [ 20 , 21 , 22 , 23 ], and adhesion contrast planography [ 24 ] have all been proposed as pattern formation techniques. Of these, we employ screen-offset printing, which is based on screen printing.…”
Section: Introductionmentioning
confidence: 99%
“…Printing is very useful technique, since it enables rapid pattern formation at low cost. Flexographic printing [ 12 , 13 , 14 ], microcontact printing [ 15 ], gravure printing [ 16 ], gravure-offset printing [ 17 , 18 ], soft blanket gravure printing [ 19 ], reverse-offset printing [ 20 , 21 , 22 , 23 ], and adhesion contrast planography [ 24 ] have all been proposed as pattern formation techniques. Of these, we employ screen-offset printing, which is based on screen printing.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the conductivity of the formed patterns relies on the concentration of AgNW. The resistance of the pure Ag pattern has a relatively high value because of electron scattering at the many contact points of the Ag granules, whereas AgNW, which is an anisotropic material with low defect density that can act as an electron highway, ensures the relatively high conductivity of the Ag/AgNW composite pattern. , Moreover, AgNWs can provide the mechanical properties to the Ag/AgNW composite pattern necessary to conform to the steps. Figure d–f shows the SEM images which illustrate the role of the AgNWs at the steps.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, our enzymebased biosensor can be fabricated using printing technology. Employing advanced printing technologies [33] will enable direct and on-demand printing of biosensing systems on threedimensional curved surfaces of conventional, existing wearable medical devices such as mouth guards, soft contact lenses, wound dressings, wristbands, and even human skin in the future. [34] Figure 1a shows the structure of the extended-gate type organic transistor device.…”
Section: Discussionmentioning
confidence: 99%